Eruptive vellus hair cyst presenting as asymptomatic follicular papules on extremities - Swapna Khatu; Resham Vasani; Shital Amin (Wolters Kluwer Medknow Publications, 2013)
Eruptive vellus hair cysts were first described in 1977. They usually appear as yellow to reddish-brown papules on the chest. Usual onset is between ages 17 and 24 years, but they may be congenital. Some believe that they may be inherited as an autosomal dominant disorder. Histologically the cyst has a stratified squamous epithelium and it contains laminated keratin and vellus hairs. They are felt to be caused by an abnormality at the infundibular level of the vellus hair. We present this because of this patient's unusual distribution of eruptive vellus hair cysts.